Reverse-Bifurcation in the Transition Process of Spherical Couette Flow - SUGAWARA, Satoshi; TSUCHIDA, Yoichi; SHA, Weiming; NAKABAYASHI, Koichi (Nihon Kikai Gakkai rombunshuu. B hen, 2002)
In the spherical Couette flow with only an inner sphere rotating, relaminarizing flow in the laminar-turbulent transition process has been investigated by the introduction of infinitesimal disturbances from the external into the supercritical flow modes with a pair of toroidal Taylor-Gortler (TG) vortices. Normal and reverse bifurcations are discussed. The onset Reynolds numbers of toroidal TG vortices, spiral TG vortices and traveling waves as well as the onset Reynolds number of the relaminarization are influenced by the external disturbances, although the critical Re of the primary instability is not influenced. Influence of the external disturbances on rms values of velocity fluctuations is greater in the relaminarizing Re-region than in the lower Re-region. Fundamental frequencies of disturbances are not influenced by the external disturbances.